Synthesis Based on Linearization of Vector Speed Control of an Induction Motor without a Speed Sensor - O. F. Opeiko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The aim of the work was parametric synthesis of vector sensorless (i. e. without speed sensor) control of an electric drive with an induction motor. The structure of the system is based on the application of an adaptive model for estimating the rotor flow coupling vector and velocity. The speed is estimated by the mismatch of the real stator current and the current value calculated in the model. Stability is guaranteed in this well-known structure, obtained on the basis of Lyapunov functions, but it remains problematic to calculate the parameters of regulators and an adaptive model to ensure high-quality dynamics of the system. For a vector control system of an induction electric motor without a speed sensor with an adaptive model, a linearized structure in a synchronously rotating coordinate system was proposed. This makes it possible to calculate control parameters using the modal control method to ensure quality indicators in each of the closed circuits of the system. Such parametric synthesis is based on the assumption that the flow coupling of the rotor is maintained constant, and therefore the mutual influence of the flow coupling and torque control channels can be neglected. The calculation of the parameters of control (regulators and the adaptation channel) is based on the method of assigning the roots of characteristic contour polynomials in such a way that each internal contour has a higher speed than the external one with respect to it. The method is approximate, but it makes it possible to take into account the main cause-and-effect relationships in dynamics and obtain simple calculation expressions. The simulation of the system was carried out using a simulation model that takes into account the digital software-algorithmic method for generating a microcontroller control signal, as well as electromagnetic processes under conditions of pulse-width modulation in an electric energy converter and an electric motor, the use of the values of the rotor flow coupling vector estimated by the model in coordinate transformations of the system, the formation of a spatial vector of the converter voltage. The analysis of the synthesized speed control system by the simulation method has confirmed the effectiveness of the proposed method of parametric synthesis and the acceptable accuracy of speed estimation.